Impacts of Coastal Development Strategies on Long-Term Coastline Changes: A Comparison Between Tampa Bay, USA and Xiangshan Harbor, China. (3rd April 2019) - Guo, Qiandong; Pu, Ruiliang; Tapley, Kimberly; Cheng, Jun; Li, Jialin; Jiao, Tong
Abstract: In recent decades rapid population growth, urbanization and industrialization have produced an intense pressure on coastal ecosystems. The coastline change is one of criteria used to denote the healthiness of coastal ecosystems. Comparison of coastline change patterns and relevant human interferences between the developed countries and the developing countries would provide insights on sustainable strategy for coastal areas. In this study, 30 years of coastline changes in Tampa Bay (TB), USA and Xiangshan Harbor (XH), China were used as an example for investigating the underlying coastal development strategies. The results indicate that coastlines in TB were mostly stable over the last 30 years. In fact, TB had experienced excessive anthropogenic impacts on its coastlines before the governments executed strict laws and regulations to control human activities. XH had been experiencing intensive human interferences and the shoreline underwent considerable changes, especially in recent years. Major anthropogenic impacts on XH coastlines are land reclamation and aquaculture, which resulted in reducing natural coastal land by approximately 20.3 km 2 . Although many developing countries are still facing the stress from population growth and economic development, enforcing strict environmental conservation rules is in an urgent need for protecting their coastal environments.